Peran Filsafat Hukum Dalam Pembentukan Hukum Di Indonesia - Himatul Ulya; Muhammad Faiz; Putri Umala; Muhammad Rian; Muhammad Lukman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The Indonesian state is based on Article 1, paragraph 3 of the 1945 Constitution that all society, its government, organs in our country must obey the laws that exist in Indonesia, and in the formation of law, legal philosophy is closely related to the philosophical aspects of law which focus on legal theory and practical problem. This includes law enforcement, conflict resolution, protection, upholding the status quo, and change to achieve a sense of justice. justice based on real and abstract legal foundations. This research uses a normative juridical research methodology, where secondary data or library sources are researched to conduct legal research through the library or online. Primary and secondary legal sources were used in this research. Primary legal sources present various relevant laws and regulations to examine how legal philosophy influences the development of Indonesian law.